Policy benefit factors for improving employee performance behavior in tourism sector companies during the covid-19 pandemic - Bambang Supriadi; Moch. Fauzie Said; Boge Triatmanto; Chandra Dinata (Jurnal Pariwisata Pesona, 2023)
Many policy initiatives and interventions in tourism have been implemented at different levels. However, compared to other sectors, tourism lags behind in adopting adequate and widely accepted evaluation methodologies. This research aims to analyze the influence of policy benefits on motivation, the effect of policy benefits having a positive and significant effect on satisfaction, the effect of policy benefits having no positive and insignificant effect on performance, the influence of motivation having a positive and significant effect on performance, and the effect of satisfaction having a positive effect. And crucial for performance. Through motivation, analyzing the impact of policy benefits has a positive and significant effect on performance. Through satisfaction, analyzing the effect of policy benefits has a positive and significant effect on performance. The research method employs a quantitative strategy. This population sample consists of 51 employees/laborers from the tourism industry in East Java. This research analysis tool employs SmartPLS with convergent validity measured by the expected average variance (AVE) value. The findings of this study indicate that satisfaction has a positive effect on performance. There is a correlation between motivation and performance. There is an effect of policy benefits on satisfaction, but none between them, and there is an effect of policy benefits on motivation.